2018
DOI: 10.1097/nmd.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Program of Psychoeducational and Psychological Rehabilitation for Patients With Bipolar Disorder in a Day Hospital Setting

Abstract: The present study describes a new mixed program of psychoeducational and psychological interventions for bipolar patients, applicable during everyday practice. Thirty-two bipolar patients recruited at a psychiatric day-hospital service have been admitted to a program consisting of 30 meetings and 2 follow-ups at 6 and 12 months. The psychoeducational support determined a general improvement of all included patients. At baseline, patients with residual depression had higher Hamilton Depression Rating Scale (HDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Recovery-focused CBT has also been shown to improve perceived personal recovery (Jones et al, 2015). Camardese et al (2018) found that a psychoeducational and psychological programme improved self-reported insight and resilience. Etain et al (2018) demonstrated improvements in knowledge about BD and illness perception following psychoeducation.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery-focused CBT has also been shown to improve perceived personal recovery (Jones et al, 2015). Camardese et al (2018) found that a psychoeducational and psychological programme improved self-reported insight and resilience. Etain et al (2018) demonstrated improvements in knowledge about BD and illness perception following psychoeducation.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies 20 , 21 and international guidelines, 22 , 23 the optimal management of BD patients should include the provision of psychoeducational family interventions (PFIs), in order to improve long-term clinical and functional outcomes of patients and their relatives. 14 , 17 19 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…In this sense, studies on intervention programs focused on psychological resilience in patients diagnosed with BPAD and with suicide attempts are insufficient. Only the article by Camardese et al (2018), which evaluated the effectiveness of an intervention program to develop psychological resilience by comparing euthymic individuals with bipolar depressive patients who were not in remission, observed a significant improvement in psychological resilience, without presenting differences between the two groups (Camardese et al, 2018).…”
Section: Discussionmentioning
confidence: 99%